Memahami watak Sa’aman dalam keluarga Gerilya: satu pendekatan logoterapi Frankl - Ratna Roshida Ab Razak (Universiti Kebangsaan Malaysia, 2010)
The purpose of this article is to secrutinise the writing of Pramoedya Ananta Toe using the Frankl logotherapy approach, that is a method of treatment for psychology disturbance through the search for the meaning of life. Logotherapy emphasises on the importance of soul and spiritualism. Keluarga Gerilya has given readers a chance to delve into the suffering and devastation of a family during the colonial era. Through his writing, the writer succeeded in transporting his readers back to the lives and sufferings of a Dutch prisoner in Bukit Duri Prison, Jakarta, Indonesia. The characters in the story are vividly pictured and they succeeded in effectively sending across a message of human dilemma and humanity in the effort to fight the Dutch colonial shackles and regain independence for their country. The vividness of Sa’aman’s character successfully invoked the readers’ empathy for the prisoners in the camp and at the same time, appreciating the true value of humanity. By exploring the spiritual strength of Sa’aman, a freedom fighter, the readers are finally able to understand the secret for his strength and perseverance. Secrutinising this masterpiece through a psychological lens, in particular through Frankl logotherapy that revolves around the importance of meaning and purpose in life, gives opportunity to the readers to better appreciate and understand the life’s journey of a nationalist’s family.